An Efficient Synthesis of Racemic Tolterodine - Sudarshan Rao, K.; Nageswara Rao, K.; Muralikrishna, P.; Jayashree, A. (Asian Journal of Chemistry, 2014)
The efficient and cost effective of the synthesis of (±)-tolterodine (1), a precursor of (+)-(R)-tolterodine was efficiently performed from 6-methyl-4-chroman-2-one (2) via 4 steps in high yield. This process is suitable for large-scale commercial production by avoiding hazardous reagents and high pressure of hydrogen gas.